Health insurance and tax policy - Karsten Jeske; Sagiri Kitao (Federal Reserve Bank of Atlanta, 2005)
The U.S. tax policy on health insurance favors only those offered a group insurance through their employers. This policy is highly regressive since the subsidy takes the form of deductions from the progressive tax system. The paper investigates alternatives to the current policy. We find that the complete removal of the subsidy results in a significant reduction in the insurance coverage and serious welfare deterioration. However, eliminating regressiveness in the group insurance subsidy and extending benefits to the private insurance market improve welfare and raise the coverage. Our work is the first in highlighting the importance of studying health policy in a general equilibrium framework with an endogenous demand for the health insurance. We use the Medical Expenditure Panel Survey (MEPS) to calibrate the process for income, health expenditure shocks, and health insurance offer status and succeed in producing the pattern of insurance demand as observed in the data, which serve as a solid benchmark for the policy experiments.
Keywords: 330; Steuerpolitik; Krankenversicherung; Theorie; USA